Repayment determinants for Egyptian microfinance institutions - Hashad, Reem Nabil (AUC Knowledge Fountain, 2014)
Finance is one of the core development axes and is the basis for job creation, income, poverty reduction and economic growth. Financial resources in Egypt are both idle and misallocated. Access to finance is a major constraint especially to the poor stratum of the Egyptian society. Microfinance is one of the means through which the poor can gain access to finance. However, Egyptian microfinance institutions (MFIs) are inefficient and are unable to supply 90% of the demand for microcredit. This research focuses on how the supply-demand gap of microcredit in Egypt can be reduced. Hence this paper examines what are the borrowers’ socio-demographic characteristics and loan conditions that affect the microcredit repayment rate in Egypt. These factors are examined so that Egyptian MFIs can be financially and socially efficient and serve as better engines for change. This paper employs the mixed method (qualitative and quantitative) approach in an attempt to answer the research question proposed. The paper estimates the log likelihood of a probit regression model based on data from two MFIs: Misr El Kheir (MEK) and Resala. In addition, interviews were conducted with twelve borrowers of one of Egypt’s MFIs (Tanmeyah). The results show that the repayment determinants are country-specific. Lack of timely repayment is both a supply-sided and demand-sided problem i.e. it is attributed to both the MFI policies and the borrowers’ characteristics. Lack of timely repayment is due to the MFI lending policies, long repayment period, the time the first installment is due, the borrower’s job, income, address and most importantly his/her willingness to pay.Macroeconomic shocks, such as the 25th of January Revolution, have positively contributed to the probability of the borrowers defaulting. Although microfinance is only a tool for poverty alleviation, not the solution, its importance can not be understated. MFIs can reduce the supply-demand gap by mitigating the reasons for lack of timely repayment such as long repayment period, lack of experience, lack of willingness to pay and so on. This will enable MFIs to revive financial resources and promote economic growth.